Ashley Vogt: capstone - Vogt, Ashley, artist (Colorado State University. Libraries, 2018)
The artist's statement: Ever since I began taking portraits in black and white film, I realized that I had something special in the way I looked at other people. My eye caught different things about their appearance, and my images allowed for some aspect of the person's personality to show through. My portraits had something that I personally found intriguing. They were mundane in-between moments, and yet they were full of life and energy. My current body of work is inspired from my first serious portrait work done in college. Beginning with a medium format, twin lens reflex camera and taking square black and white images, I then transitioned into color film and my pictures took on new life and meaning. Now I have transitioned again and tried my hand at full frame digital capture in color. I have also gone from outdoor image making to working in a studio setting. My hope is that these images engage and allow the viewer into the personal space of the person pictured, giving them some insight to a person they have never met before.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photo image making